2012
DOI: 10.1177/0961203312443992
|View full text |Cite
|
Sign up to set email alerts
|

Decreased breast cancer risk in systemic lupus erythematosus: the search for a genetic basis continues

Abstract: Within this large breast cancer dataset, we did not demonstrate important associations with 10 lupus-associated SNPs. If decreased breast cancer risk in SLE is influenced by genetic profiles, this may be due to complex interactions and/or epigenetic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Earlier, we used general population breast cancer genome-wide association study (GWAS) data, to explore whether single nucleotide polymorphisms (SNPs) predisposing to SLE might be protective against breast cancer (in women in the general population)[19]. We focused on loci relevant to 10 SNPs that are highly associated with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we used general population breast cancer genome-wide association study (GWAS) data, to explore whether single nucleotide polymorphisms (SNPs) predisposing to SLE might be protective against breast cancer (in women in the general population)[19]. We focused on loci relevant to 10 SNPs that are highly associated with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of chronic autoimmunity on the natural history of solid tumors is not well understood. For example, although SLE patients have decreased risk of breast cancer and melanoma (23), the underlying mechanisms and biological significance of these observations are unclear. It may be relevant that longitudinal analyses of sera from long-term surviving melanoma patients after vaccination with GM-CSF-secreting autologous melanoma cells have revealed that the generation of autoantibodies was associated with increased tumor destruction (15).…”
Section: Discussionmentioning
confidence: 99%
“…SLE is associated with an overall increased risk of malignancy, but lower than expected rates of tumors associated with defects in BRCA2 such as breast, ovarian, and prostate cancers141516. The pathophysiology underlying this risk profile is unknown and is likely multifactorial1718. We previously suggested that cell-penetrating lupus autoantibodies such as 3E10 that inhibit DNA repair might contribute to this phenomenon by suppressing growth of BRCA2- cells6, and our present findings now raise the possibility that nucleolytic lupus autoantibodies may also contribute to inhibiting the growth of BRCA2-associated tumors in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%